(untitled) - Marcus, Alfred Allen (New York, 2011)
Focuses on how making winning moves depends on finding profitable patterns that meet customer demands for solutions. This book emphasizes the types of analyses and strategic moves required, given the industry, environment, and a company's internal resources. It demonstrates how strategy impacts an organization's position.
Keywords: Strategic planning,Management,Lập kế hoạch chiến lược,Quản lý